Pengaruh Tingkat Usia dan Pendidikan Masyarakat Kepulauan Seribu Terhadap Pengetahuannya Mengenai Konservasi Laut - Lina Mariyana; Supardi U.S. (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to determine the influence of the age level of Kepulauan Seribu community on their knowledge of marine conservation, the influence of the education level of Kepulauan Seribu community on their knowledge of marine conservation, and the interaction between the age level and education of Kepulauan Seribu community on their knowledge of marine conservation. This research was conducted in Pramuka Island, Pulau Panggang, Kepulauan Seribu. The method used is ex post facto with a sample number of 60. The sample was divided into groups based on age level and education. The instrument used is a marine conservation knowledge test of 45 questions in the form of multiple choice with four alternative answers. The hypothesis was tested using the F test via bidirectional ANAVA at a=0.05. The ratio of F between columns has Fcount=0.097 which is smaller than Ftable=3.19. This means that there is no influence on the age level of the Thousand Islands community on their knowledge of marine conservation. The ratio of F between rows has Fcalculate = 3.915 greater than Ftable = 2.80. This shows that the level of education affects the knowledge of the Thousand Islands community about marine conservation. The ratio F of column and row interaction has Fcount=1.206 which is smaller than Ftable=2.30. So there is no influence of interaction between the age level and education of the people of Thousand Islands on their knowledge about marine conservation. The results of this research are expected to be a thought for all parties to pay attention to educational activities in the Thousand Islands both formally and informally. This is important because most of Indonesia consists of oceans and its conditions are increasingly threatened.